Advances in protein chemistry (Academic Press, 1998)
This volume commemorates the 50th anniversary of the appearance in Volume 4 in 1948 of Dr. Jeffries Wyman's famous paper in which he "laid down" the foundations of linkage thermodynamics. Experts in this area contribute articles on the state-of-the-art of this important field and on new developments of the original theory. Among the topics covered in this volume are electrostatic contributions to molecular free energies in solution; site-specific analysis of mutational effects in proteins; allosteric transitions of the acetylcholine receptor; and deciphering the molecular code of hemoglobin allostery.